3x – 1 – x = 3x + 5

Question

Asked 11/13/2011 7:49:11 PM

Updated 5/13/2014 4:15:54 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [5/13/2014 4:15:54 AM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

sharpies|Points 4928|

Question

Asked 11/13/2011 7:49:11 PM

Updated 5/13/2014 4:15:54 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [5/13/2014 4:15:54 AM]

Rating

8

3x – 1 – x = 3x + 5;

2x - 1 = 3x + 5;

2x - 3x = 5 + 1;

-x = 6;

x = -6

2x - 1 = 3x + 5;

2x - 3x = 5 + 1;

-x = 6;

x = -6

Added 5/13/2014 4:15:49 AM

This answer has been confirmed as correct and helpful.

5(x + 3)=7(x – 5)

Question

Updated 11/13/2011 8:17:41 PM

2 Answers/Comments

The answer to the equation: 5(x + 3)=7(x – 5) is to rewrite the equation as 5x + 15=7x – 35 and then adding like variables: 50=2x and then solving for x which is x=25.

Added 11/13/2011 8:17:41 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/1/2014 1:25:45 PM]

5(x+3)=7(x–5) solve for x User: Graph the equation Y = 4x – 3 **Weegy:** Sorry can't show the graph. But here are the values. x=1, y= 1/ x=2, y=5. **User:** Graph the equation 4x – 5 = 2x – y **User:** 4x – 5 = 2x – y **Weegy:** 5/2x+1/4x=7/4+x SOLUTION:
5/2x+1/4x-x=7/4 >>
(5/2+1/4-1)x=7/4 >>
(7/4)x=7/4 >>
x=(7/4)/(7/4) >>
x=1 **User:** graph 4x – 5 = 2x – y **Weegy:** Sorry but I cannot graph that equation since we don't have a tool to attach a file on our answers (More)

Question

Expert Answered

Updated 3/14/2012 8:14:11 AM

1 Answer/Comment

5(x+3)=7(x–5) solve for x

5x+15 = 7x -35

5x-7x = -15-35

-2x = -50

x = 25

5x+15 = 7x -35

5x-7x = -15-35

-2x = -50

x = 25

Added 3/14/2012 8:14:11 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/16/2014 12:28:23 PM]

solve 15x + 2 = 9x + 28 **Weegy:** 15x + 2 = 9x + 28, 15x - 9x = 28 - 2, 6x = 26, x = 26/6, x = 4 2/6, simplified: x = 4 1/3
(More)

Question

Expert Answered

Asked 11/16/2011 4:57:03 PM

0 Answers/Comments

3x – 1 – x = 3x + 5

Question

Not Answered

Updated 7/1/2014 1:25:31 PM

1 Answer/Comment

The answer to the equation 3x – 1 – x = 3x + 5 is to first add and subtract like terms: 3x-x-3x=1+5 so -x=6 which is x= -6.

Added 11/13/2011 8:36:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/1/2014 1:25:34 PM]

2x+4=28 show all work **Weegy:** Solving for x. First we move like term to different sides of eq. so we leave the 2x where it is, because it's the only one, and we move the 4 to the right side as a negative 4. Now we have 2x=28-4 which is 2x=24. [ Then we proceed to get rid of the 2 to leave the x alone by diving both sides by 2. So now we have 2x/2=24/2. That should give us: x=12 ] (More)

Question

Expert Answered

Updated 4/14/2014 11:32:55 AM

1 Answer/Comment

2x+4=28;

2x = 28 - 4;

2x = 24;

x = 24/2;

x = 12

2x = 28 - 4;

2x = 24;

x = 24/2;

x = 12

Added 4/14/2014 11:32:55 AM

This answer has been confirmed as correct and helpful.

39,505,459

questions answered

There are no comments.